A scoping review of behaviour change theories in adults without dementia to adapt and develop the 'PHYT in dementia', a model promoting physical activity in people with dementia. (March 2019) - Di Lorito, Claudio; Pollock, Kristian; Harwood, Rowan; das Nair, Roshan; Logan, Pip; Goldberg, Sarah; Booth, Vicky; Vedhara, Kavita; Van Der Wardt, Veronika
Highlights: There is no model of behaviour change in relation to physical activity for people with dementia. From a review of theories, we derived an integrated model for people with dementia. The model synthesises individual-level and social ecological theories previously used for behaviour change in healthy adults. We called our model the 'PHYT in dementia'. We will test our model empirically and refine it if necessary. Abstract: Introduction: Research has established that exercise and physical activity can improve executive functioning, independence and quality of life in people with dementia. A dedicated theory explaining behaviour change in relation to physical activity in people with dementia does not exist. We aimed to develop a theoretical model which can be used to inform effective interventions to promote physical activity in people with dementia. Methods: There were five phases: 1. A search of the literature to identify theories which have been used to explain behaviour change in relation to physical activity in adult populations without a diagnosis of dementia; 2. Description of the theories (and sub-theories) and their main constructs; 3. Synthesis of the constructs; 4. Adaptation of the constructs to dementia; 5. Development and explanation of a model for physical activity in people with dementia (the 'PHYT in dementia'). Results: We identified nine theories used to explain behaviour change in relation to physical activity in adult populations without a diagnosis of dementia. Through our synthesis, we identified nine umbrella constructs. We integrated three more dementia-relevant constructs and developed the 'PHYT in dementia'. The model was explained by providing a practical example of its application. Discussion: Based on a scoping review of behaviour change theories in adults without dementia and following adaptation of the constructs from these theories to dementia, we derived a new theoretical model, the 'PHYT in dementia', which includes both individual-level and environment-level constructs. The model needs to be tested empirically, which our research team will do in the process evaluation of the Promoting Activity, Independence and Stability in Early Dementia and Mild Cognitive Impairment (PrAISED 2) study. Results from field-testing will inform refinement of the model.